2014
DOI: 10.1631/jzus.b1400130
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between post-operative cognitive dysfunction and regional cerebral oxygen saturation and β-amyloid protein

Abstract: Abstract:Objective: To investigate the relationship between post-operative cognitive dysfunction (POCD) and regional cerebral oxygen saturation (rSO 2 ) and β-amyloid protein (Aβ) in patients undergoing laparoscopic pancreaticoduodenectomy. Methods: Fifty patients undergoing elective laparoscopic pancreaticoduodenectomy received five groups of neuropsychological tests 1 d pre-operatively and 7 d post-operatively, with continuous monitoring of rSO 2 intra-operatively. Before anesthesia induction (t 0 ), at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The diagnoses of POCD now mainly rely on neuropsychological testing, but there is not yet a unified standard for a POCD neuropsychological test (Li et al, 2014). The commonly used tests are MMSE, the Wechsler Adult Intelligence Scale (WAIS), and the Wechsler Memory Scale (WMS).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnoses of POCD now mainly rely on neuropsychological testing, but there is not yet a unified standard for a POCD neuropsychological test (Li et al, 2014). The commonly used tests are MMSE, the Wechsler Adult Intelligence Scale (WAIS), and the Wechsler Memory Scale (WMS).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researchers have tried to find ideal biological markers associated with the POD to reduce its occurrence. Aβ and Tau proteins, as biochemical indicators, are the main markers in the pathogenesis of POCD ( Li et al, 2014 ). Some studies have also confirmed that preoperative CSF Aβ and Tau in patients with geriatrics are significantly correlated with the changes in postoperative cognitive function ( Wu et al, 2018 ), consistent with this study.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the study of POCD biochemical markers has become a focus issue. Aβ and Tau protein, as one of the biochemical indicators, are the main markers of the pathogenesis of POCD [20].Some studies have also con rmed that the preoperative cerebrospinal uid Aβ and Tau in elderly patients are signi cantly correlated with the changes of postoperative cognitive function [21].Progranulin (PGRN) is a multifunctional growth factor expressed in a variety of tissues and involved in many physiological and pathological processes [22]. It is widely expressed in various cells of the body.…”
Section: Discussionmentioning
confidence: 99%